Growth responses of oil palm seedling inoculated with Ganoderma boninense under competition with edible herbaceous plants - Rahmadhani, Tiara Putri; Suwandi, Suwandi; Suparman, Suparman (Journal of Scientific Agriculture, 2020)
Basal stem rot (BSR) caused by long-term survival fungus Ganoderma boninense is the most important of oil palm disease that difficult to be controlled. Perennial herbaceous species are potentially developed for long-term BSR control and applied as mixed planting with oil palm. This research was aimed to study the competition effects of mixed planting with edible herbaceous perennial plants (edible canna (Canna indica), arrowroot (Maranta arundinacea), cocoyam (Xanthosoma sagittifolium), and water yam (Dioscorea alata) on growth of oil palm seedlings. Two competition trials (non-inoculated and Ganoderma-inoculated trial) were conducted. The herbaceous plants were grown together with oil palm seedling in a polybag filled with 40 L field soil. Mixed planting of Ganoderma-inoculated oil palm and herbaceous plants and grown on a large soil volume resulted in a minor infection with a high variation in severity leading to insignificant effect of herbaceous competition on Ganoderma infection. Herbaceous competition significantly suppressed oil palm seedling growth under both inoculated with Ganoderma and without inoculation. Arrowroot exhibited as the most competitive herbaceous species and followed by canna and cocoyam. Water yam showed a weak competitive against oil palm seedling since only a minor interference in all observed growth characteristics.